Polyurea-crosslinked biopolymer aerogel beads. Issue 67 (9th November 2020) - Paraskevopoulou, Patrina; Smirnova, Irina; Athamneh, Tamara; Papastergiou, Maria; Chriti, Despoina; Mali, Gregor; Čendak, Tomaž; Raptopoulos, Grigorios; Gurikov, Pavel
Abstract : Polyurea-crosslinked calcium alginate and chitosan aerogel beads: novel fibrous biopolymer-based aerogels. Abstract : Polyurea-crosslinked calcium alginate (X-Ca-alginate) and chitosan (X-chitosan) aerogel beads have been prepared via reaction of an aliphatic triisocyanate (Desmodur N3300) with the –OH groups of calcium alginate or the –NH2 groups of chitosan preformed wet gels, forming surface urethane or urea groups, respectively, and the subsequent formation of a polyurea conformal coating of the network via reaction of the triisocyanate with adsorbed water retained on the inner surfaces of the wet gels. That conformal coating is evident by SEM, which showed that all aerogels, native and crosslinked, were fibrous and their micromorphology did not change after crosslinking. The chemical identity of the new materials was confirmed with ATR-FTIR spectroscopy and solid-state 13 C and 15 N CPMAS NMR spectroscopy. The percent uptake of polyurea in X-Ca-alginate aerogels (43–66%) and X-chitosan aerogels (31–51%) was calculated from skeletal density data. This work expands the methodology for polymer-crosslinked alginate aerogels from monoliths to beads, and from alginates to chitosan, establishing its generality for all biopolymer aerogels. Possible applications of these materials include environmental remediation and conversion to carbon aerogels.